2011
DOI: 10.1021/ac200842e
|View full text |Cite
|
Sign up to set email alerts
|

Development of Submillisecond Time-Resolved Mass Spectrometry Using Desorption Electrospray Ionization

Abstract: Reaction kinetics studied by mass spectrometry (MS) has previously been limited to millisecond time resolution. This paper presents the development of a submillisecond time-resolved mass spectrometric method for fast reaction kinetic study, based on the capability of desorption electrospray ionization (DESI) for direct and fast ionization of a high-speed liquid jet stream. The principle underlying this methodology is that two reactant solutions undergo rapid mixing to produce a free liquid jet which is ionized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 40 publications
1
50
0
2
Order By: Relevance
“…Time-resolved mass spectrometry (11) has been widely used for measuring the kinetics of protein-ligand complexation, organometallic compound formation, and enzyme-catalyzed processes. Despite these efforts for improving temporal resolution, time-resolved mass spectrometry has been limited to the millisecond timescale, with a recent achievement of 300 μs (12).…”
mentioning
confidence: 99%
“…Time-resolved mass spectrometry (11) has been widely used for measuring the kinetics of protein-ligand complexation, organometallic compound formation, and enzyme-catalyzed processes. Despite these efforts for improving temporal resolution, time-resolved mass spectrometry has been limited to the millisecond timescale, with a recent achievement of 300 μs (12).…”
mentioning
confidence: 99%
“…1, 5 of CTH in bulk reaction mixtures (reaction time of a few minutes) (15). Ambient ionization methods (24)(25)(26) such as desorption electrospray ionization (DESI) (27)(28)(29) provide a simpler approach to intercepting reactive species without prior sample preparation (30)(31)(32)(33)(34)(35). We recently demonstrated that DESI can intercept CTH intermediates in solution on the millisecond time scale (36).…”
mentioning
confidence: 99%
“…AMS provides the ability to perform chemical analyses of systems in their natural state, which has led to impactful discoveries in numerous research areas such as forensics, environmental science, and cancer biochemistry [45][46][47][48][49][50][51][52][53]. Recently, Chen and coworkers [11,[54][55][56][57][58] demonstrated that DESI can characterize liquid samples (liquid sampling DESI; LS-DESI) such as the effluent from chromatographic columns [59][60][61] and EC flow-cells [10,[62][63][64]. When microdroplets from a LS-DESI source impact the outlet of tubular [54] or thin layer [10] EC flow cells, species in the EC effluent are desorbed into secondary microdroplets that travel towards a MS for detection.…”
Section: Introductionmentioning
confidence: 99%